Reduction of Audit Quality by Auditors of Small and Medium Size Audit Firms in Malaysia: A Case of Premature Sign-Off of Audit Documents - Khairunnisa Mohd Jais; Anuar Nawawi; Ahmad Saiful Azlin Puteh Salin (STIE Malangkucecwara, 2016)
Premature sign-off of audit documents (premature sign-off) is one of the behaviours of external auditors in the audit progress that will reduce quality of an audit program. The purposes of this study are to examine whether external auditors commonly practice premature sign-off and to investigate the factors contributing to these practices. In addition, the impact of premature sign-off is also evaluated. This study is based on the primary data of survey questionnaires among the external auditors as the data collection method. This study found that premature sign-off was commonly practiced by almost half of the respondents in the survey. This practices causes by rush audit work, overdependence on regular corporate clients, allocation of inadequate number of audit hours and insufficient supervision by senior auditors. Almost all respondents agree that the premature sign-off of audit documents by external auditors affect the confidence of the users in the credibility of audit report and hence, truthfulness of the financial statement.